Staging Statecraft: Dance Festivals and Cultural Representations in Konark, Odisha, India - Mihika Banerjee (Arts, 2024)
This essay argues that dance festivals are choreographed spaces that shape cultural heritage. The Konark Dance Festival in Odisha, India, is an annual program situated around the Konark Sun Temple, a UNESCO-recognized World Heritage Site. The following explores the interrelationship between the modern space of the temple monument and the modern format of festival dances in Konark. The festival project juxtaposes the monument’s archaeological value with the dances’ cultural value in choreographic neatness, which requires a critical interrogation to determine the negotiations, appropriations, and discomfort these processes otherwise entail. This article also branches out into cultural discourses beyond the stated festival that examine the historical, diplomatic, and touristic networks the dance festival often encompasses. Following the creation of the modern state of Odisha (in 1936) and of the independent nation of India (in 1947), Odisha regional dance forms were remodelled to produce the state dance Odissi, which gained national “classical” recognition in the 1960s and subsequent international repute. Odissi dance has subsequently been formulated and globally circulated as an anthropomorphic symbol of the geopolitical state of Odisha. Through ethnography, visual study, and choreographic analysis, this essay explores the (re)presentational aspects of the region-state in and through dance, which rhetorically inform the staging of the Konark Dance Festival.